Electrochemiluminescence of Supramolecular Nanorods and Their Application in the "On-Off-On" Detection of Copper Ions - Lei, Yan-Mei; Zhao, Min; Wang, Ai; Yu, Yan-Qing; Chai, Ya-Qin; Yuan, Ruo; Zhuo, Ying (Chemistry : a European journal, 2016)
In this work, an “on–off–on” switch system has been successfully applied through the construction of an electrochemiluminscent biosensor for copper ion (Cu2+) detection based on a new electrochemiluminescence (ECL) emitter of supramolecular nanorods, which was achieved through supramolecular interactions between 3,4,9,10‐perylenetetracarboxylic acid (PTCA) and aniline. The initial “signal‐on” state with strong and stable ECL emission was obtained by use of the supramolecular nanorods with a new signal amplification strategy involving a co‐reaction accelerator. In addition, ECL quencher probes (Fc‐NH2/Cu‐Sub/nano‐Au) were fabricated by immobilizing aminoferrocene (Fc‐NH2) on Cu‐substrate strand modified Au nanoparticles. The quencher probes were hybridized with the immobilized Cu‐enzyme strand to form Cu2+‐specific DNAzyme. Similarly, the “signal‐off” state was obtained by the high quenching effect of Fc‐NH2 on the ECL of the excited‐state PTCA (1PTCA*). As expected, the second “switch‐on” state could achieved by incubating with the target Cu2+, owing to the Cu2+‐specific DNAzyme, which was irreversibly cleaved, resulting in the release of the quencher probes from the sensor interface. Herein, on the basis of the ECL intensity changes (ΔIECL) before and after incubating with the target Cu2+, the prepared Cu2+‐specific DNAzyme‐based biosensor was used for the determination of Cu2+ concentrations with high sensitivity, excellent selectivity, and good regeneration. Copper switching: An “on–off–on” switch system has been successfully applied through the construction of an electrochemiluminscent biosensor for copper(II) ions based on a new electrochemiluminescence (ECL) emitter made of supramolecular nanorods, which was achieved through supramolecular interactions between 3,4,9,10‐perylenetetracarboxylic acid (PTCA) and aniline (An; see scheme).